RETRACTED: Geochemistry of nitric thermal springs from Khoja-Obi-Garm thermal area (Pamir-Tien Shan region) - Kharitonova Natalia; Baranovskaya Ekaterina; Chelnokov George; Bragin Ivan; Salikhov Farid; Funikova Victoria (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001